Suppression of the Viability and Proliferation of HepG2 Hepatocellular Carcinoma Cell Line by Konjac Glucomannan - Sawai, Sakunie; Mohktar, Mas Sahidayana; Wan Kamarul Zaman, Wan Safwani; Ramasamy, Thamil Selvee (Bentham Science Publishers, 2019)
BACKGROUND: Konjac Glucomannan (KGM) is a water-soluble dietary fibre extracted from Amorphophallus konjac K. Koch (Araceae). Konjac fibre has been clinically proven as an effective antioxidant agent in weight control but its traditionally known tumour suppression property remains to be explored. OBJECTIVE: The main objective of this study is to determine the potential anti-proliferative effect of KGM on cancer and normal human liver cell lines, HepG2 and WRL68, respectively. METHOD: HepG2 and WRL68 cells were treated with KGM, D-mannose, KGM-D-mannose and 5-fluorouracil. The morphological changes in those treated cells were observed. Cytotoxic effect of the treatments on cell viability and proliferation, and apoptosis genes expression were assessed by cytotoxicity assay, flow cytometry and RT-PCR analyses. RESULTS: The results show that KGM treatment resulted in reduced viability of HepG2 cells significantly, in line with the apoptosis-like morphological changes. Up-regulation of BAX and down-regulation of BCL2 genes as reflected by high Bax to Bcl 2 ratio suggests that the inhibitory effect of KGM on HepG2 cells most likely via Bcl2/Bax protein pathway. Despite the effectiveness of standard drug 5-FU in suppressing the viability and proliferation of HepG2 cells, it however, exhibited no selective inhibition of cancer cells as compared to KGM. CONCLUSION: Current findings suggested that KGM is a potential anti-cancer compound/drug entity, which could be an alternative preventive agent against liver cancer.